Indonesia Data Protection in the Use of M-Banking, Is It Save? - Suran Ningsih, Ayup (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 3 (2021)DO - 10.24843/JMHU.2021.v10.i03.p01, 2021)
Banking is one of the institutions in the financial sector that provides services to users and customers. The development of science, information, and technology, makes it easy to develop the banking system itself, by developing systems and services that aim to provide facilities and pamper its customers. With regard to flexibility, efficiency and practicality. Thus, was born a new method in developing banking services for customers, where the system is called electronic banking, or usually with the term e-banking which allows customer service users to use it, anywhere and anytime, not limited by time with the service. As for the making of this journal, he uses an approach to the type of normative legal research, where research is carried out in research conducted by examining library materials related to this issue. The problem raised by the author is how the normative juridical review is related to the protection of bank users using M-Banking from the threat of crime in the digital world and what forms of legal protection are for bank customers in the use of M-Banking. So that through this paper, it is hoped that it will be useful for the protection of the public so that customers become safer.